A rapid and efficient synthetic route to terminal arylacetylenes by tetrabutylammonium hydroxide- and methanol-catalyzed cleavage of 4-aryl-2-methyl-3-butyn-2-ols - Li, Jie; Huang, Pengcheng (Beilstein Journal of Organic Chemistry, 2011)
Tetrabutylammonium hydroxide with methanol as an additive was found to be a highly active catalyst for the cleavage of 4-aryl-2-methyl-3-butyn-2-ols. The reaction was performed at 55–75 °C and gave terminal arylacetylenes in good to excellent yields within several minutes. Compared with the usual reaction conditions (normally >110 °C, several hours), this novel catalyst system can dramatically decrease the reaction time under much milder conditions.
Keywords: 4-aryl-2-methyl-3-butyn-2-ol; deprotection reaction; 2-methyl-3-butyn-2-ol; terminal alkynes; tetrabutylammonium hydroxide